2013
DOI: 10.1097/hp.0b013e31828ca73a
|View full text |Cite
|
Sign up to set email alerts
|

Workshop Report on Atomic Bomb Dosimetry—RESIDUAL Radiation Exposure

Abstract: There is a need for accurate dosimetry for studies of health effects in the Japanese atomic bomb survivors because of the important role that these studies play in worldwide radiation protection standards. International experts have developed dosimetry systems, such as the Dosimetry System 2002 (DS02), which assess the initial radiation exposure to gamma rays and neutrons but only briefly consider the possibility of some minimal contribution to the total body dose by residual radiation exposure. In recognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…These various materials include ceramic roof tiles, soil mortar used to set the roof tiles, bricks, concrete, wood, and mud plaster on the interior walls of houses. Several neutron-activation studies have shown that the most significant radionuclides produced in these urban materials are essentially the same as those found in the neutron-activated soils at Hiroshima and Nagasaki (Arakawa 1962;Hashizume et al 1969;Endo et al 2013). Thus, the radioactive decay curves have been found to be approximately the same for soil and other materials lofted upward by the reflected shock wave and the following upward draft of the buoyant fireballs from the explosions.…”
Section: Neutron Activated Radionuclides From Dust Stem and Pedestalmentioning
confidence: 79%
See 2 more Smart Citations
“…These various materials include ceramic roof tiles, soil mortar used to set the roof tiles, bricks, concrete, wood, and mud plaster on the interior walls of houses. Several neutron-activation studies have shown that the most significant radionuclides produced in these urban materials are essentially the same as those found in the neutron-activated soils at Hiroshima and Nagasaki (Arakawa 1962;Hashizume et al 1969;Endo et al 2013). Thus, the radioactive decay curves have been found to be approximately the same for soil and other materials lofted upward by the reflected shock wave and the following upward draft of the buoyant fireballs from the explosions.…”
Section: Neutron Activated Radionuclides From Dust Stem and Pedestalmentioning
confidence: 79%
“…The basic grains within these soil particles can range in size from a few microns to several centimeters in diameter (Spriggs and Ray-Maitra 2007;Endo et al 2013;Sakaguchi et al 2013). The radial turbulent diffusion in this trailing stem removes the largest particles from the updraft, and these will fall to the ground from the heights to which they were lofted.…”
Section: Fission Products and Weapon Debris From The Nuclear Cloudmentioning
confidence: 99%
See 1 more Smart Citation
“…Further examination of the differences between measured and calculated values of gamma dose was undertaken at two recent workshops (Kerr et al, 2013 andKerr et al, 2015). Notwithstanding the overall agreement obtained between the luminescence and calculated values of free-in-air kerma with ground distance over a range of three orders of magnitude of dose (Fig.…”
Section: Ds02 Follow-upmentioning
confidence: 95%
“…Cullings et al (2006) provide an informative overview of the key stages of the evolution of the dosimetry system (DS), and details of these are given in a series the published reports, including the initial tentative dosimetry system T65D (Milton and Shohoji, 1968), DS86 (Roesch, 1987) and the current system, DS02 (Young and Kerr, 2005). A series of interleaved workshops have served to review and develop agendas for further improvement of the dosimetry system (Kerr et al, 2015 andKerr et al, 2013).…”
Section: Hiroshima and Nagasakimentioning
confidence: 99%